The Effect of the SDKI, SLKI, and SIKI Education Program on Nurses' Attitudes on Nursing Documentation - Umboh Morenita Jeanifer; Ati Surya Mediawati; Irman Somantri (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
Standardized nursing language must be accurately communicated between nurses and other healthcare professionals. Based on the Decree of the Minister of Health of the Republic of Indonesia Number HK.01.07/MENKES/425/2020 concerning professional standards for nurses, the documentation of nursing care refers to Indonesian nursing diagnosis standard (SDKI), Indonesian nursing outcomes standard (SLKI), Indonesian nursing intervention standard (SIKI). This study aimed to determine the effect of the Indonesian nursing diagnosis standard (SDKI), Indonesian nursing outcomes standard (SLKI), Indonesian nursing intervention standard (SIKI) education program’s goal attainment and interaction approach of Imogene M. King’s theory on nurses’ attitudes toward nursing documentation in the Inpatient Room. The method of this study was quasi-experimental with one group pre-test and post-test design. The sampling technique used a total sampling of 41 nurses. The analysis implemented the Wilcoxon Signed Test. The results showed differences in nurses’ attitudes toward cognitive aspects (p-value, 0.002<0.05), nurses’ attitudes toward affective aspects (p-value, 0.001<0.05), and nurses’ attitudes toward conative of the Indonesian Nursing Diagnosis standard (SDKI) nursing documentation (p-value, -0.001<0.05). There are differences in nurses’ attitudes toward cognitive aspects (p-value, 0.001<0.05), nurses’ attitudes toward affective aspects (p-value, -0.001<0.05), and nurses’ attitudes toward conative aspects of the Indonesian nursing output standard (SLKI) nursing documentation (p-value, -0.001<0.05). There are differences in nurses’ attitudes toward cognitive aspects (p-value, -0.001<0.05), nurses’ attitudes toward affective aspects (p-value, -0.001<0.05), and nurses’ attitudes toward conative aspects of the Indonesian nursing intervention standard (SIKI) nursing documentation (p-value, -0.001<0.05).